Nano Drug Delivery System with Resveratrol as Promising Novel Adjuvant Therapy for Diabetic Non-Healing Wounds: A Literature Review - Sari, Ni Wayan Puspita; Els, Vanessa; Indrayani, Agung Wiwiek (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Diabetes mellitus (DM) is a metabolic disease characterized by increased blood sugar levels (hyperglycemia) and is associated with impaired function of β cells. The uncontrolled and prolonged hyperglycemia in DM can cause complications. One of the most common is diabetic non-healing wounds, the leading cause of disability in people with diabetes, therefore adjuvant therapy is needed. Compounds from natural ingredients are currently getting the spotlight in recent studies conducted to prove their effect on non-healing wounds, such as Resveratrol (RSV). This review aims to discuss the potential of RSV as a novel adjuvant therapy and its delivery system strategy in the case of diabetic non-healing wounds. We conducted an extensive search from three online scientific databases such as ScienceDirect, ResearchGate, and PubMed on February-March 2023. Keywords used are "resveratrol", "diabetic wound healing", and "diabetes mellitus". As a result, 86 studies were reviewed, and only 79 selected studies met all inclusion criteria. The formulation of RSV nanoparticles in oral drug delivery systems and topical administration has shown promise to overcome the limitations of RSV as adjuvant therapy in diabetic non-healing wounds. The best option that we found through this literature review is the nano-oral drug delivery system as it could minimize drug metabolism in the gastrointestinal tract, therefore the drug bioavailability and drug concentration on the target site could be maximized, even though the systemic side effects might occur.